Морфобіологічні особливості Trifolium ambiguum Bieb. у фазах цвітіння й плодоношення в умовах Лісостепу України - Solonenko, V.I. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2002)
Peculiarities of flowering and fruiting phases of Trifolium ambiguum Bieb. are studied. Numeration of racemes is elaborated and biological value of flowering and fruiting phases in conditions of inflorescence in composition of generative stem is determined.